Stimulating trust cooperation in edge services: An evolutionary tripartite game. (November 2022) - Sun, Panjun; Shen, Shigen; Wu, Zongda; Zhou, Haiping; Gao, Xiao-Zhi
Abstract: Network edge services have contributed to ordinary people's daily lives with numerous conveniences but the accompanying problems, such as counterfeiting, the trust crisis and the service provider' s lack of standardization, have created some turmoil in the industry. Trust is crucial to network services, and the responsibilities of a platform's trust supervision can no longer be ignored. To enhance trust and cooperation among service participants, this paper constructs a new tripartite game model of monitors, edge service providers (ESPs) and users. First, this paper discusses the characteristics of the players in the edge service game and establishes a tripartite payment matrix model. Second, this paper outlines the concept of an evolutionary stability strategy, analyzes how to apply the dynamic replication equation to calculate the equilibrium solution and obtains the phase diagrams of the monitor, ESP, and the user. The ideal stable state point active monitoring, honesty, trust is obtained by calculating the value of an eigenvalue less than zero in the Jacobian matrix. Finally, this paper designs relevant experimental studies to verify and compare the correctness and effectiveness of several factors that affect the convergence stability of the evolutionary games, compares them with other research models, considers some advantages and discusses future development directions.